2010
DOI: 10.1021/ja909769a
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Aggregation: Formation and Transformation of Mesocrystal Intermediates Revealed

Abstract: Oriented aggregation is a special case of aggregation in which nanocrystals self-assemble and form new secondary single crystals. This process has been suggested to proceed via an intermediate state known as the mesocrystal, in which the nanocrystals have parallel crystallographic alignment but are spatially separated. We present the first direct observations of mesocrystals with size and shape similar to product oriented aggregates by employing cryo-TEM to directly image the particles in aqueous suspension. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
334
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 287 publications
(349 citation statements)
references
References 15 publications
11
334
1
1
Order By: Relevance
“…Because transformation of osmotic to crystalline hydrates involves assembly of individual smectite 2:1 layers in solution, it can be classified as an example of oriented attachment-based crystal growth (OA) (Penn and Banfield, 1998). Such OA has been reported as a crystal-growth mechanism for many poorly soluble nanoparticulate minerals, including oxides and sulfides (Penn et al, 2001;Huang et al, 2003), and has been observed in suspensions of nanoparticles with a range of morphologies (Yuwono et al, 2010;Frandsen et al, 2014). The case of assembly of 2:1 smectite layers is distinct from other growth processes described as OA because the attachment process is readily reversible due to the unusually low strength of layerÀlayer interactions (because attachment does not involve the formation of covalent or ionic bonds).…”
Section: Long-range Attractive Interactions Spanning Multiple Smectitmentioning
confidence: 99%
See 1 more Smart Citation
“…Because transformation of osmotic to crystalline hydrates involves assembly of individual smectite 2:1 layers in solution, it can be classified as an example of oriented attachment-based crystal growth (OA) (Penn and Banfield, 1998). Such OA has been reported as a crystal-growth mechanism for many poorly soluble nanoparticulate minerals, including oxides and sulfides (Penn et al, 2001;Huang et al, 2003), and has been observed in suspensions of nanoparticles with a range of morphologies (Yuwono et al, 2010;Frandsen et al, 2014). The case of assembly of 2:1 smectite layers is distinct from other growth processes described as OA because the attachment process is readily reversible due to the unusually low strength of layerÀlayer interactions (because attachment does not involve the formation of covalent or ionic bonds).…”
Section: Long-range Attractive Interactions Spanning Multiple Smectitmentioning
confidence: 99%
“…The flash freezing approach has been proven to preserve the structure of hydrated biological macromolecules such as ribosomes for which independent atomic-resolution structures exist (see Cheng, 2015, and references therein). Cryo-TEM has previously been used to determine the structure of microbial mineral precipitates (Comolli et al, 2011) and the structure of fragile, extended aggregates of Fe oxyhydroxide nanoparticles (Yuwono et al, 2010;Frandsen et al, 2014;Legg et al, 2014). Cryo-TEM was used by Segad et al (2012) to compare the aggregate structures of Na-and Ca-equilibrated montmorillonite suspensions, but without investigating the osmotic hydrate regime.…”
Section: Introductionmentioning
confidence: 99%
“…OA has been inferred for metals (10), semiconductors (11), and insulating oxides (6); it has been directly observed via liquid phase transmission electron microscopy (LP-TEM) (5), and the evolution of particle distributions during OA has been captured with cryogenic TEM (12). OA is highly dependent on solution conditions, including pH, ionic strength, and temperature, and is marked by two important stages.…”
mentioning
confidence: 99%
“…In the first stage, particles approach one another but do not make contact; rather they remain separated by an intervening solvent layer of O(1) nm in thickness (5). This solvent-separated state can occur on such an extensive scale that a kinetically stabilized particle array-sometimes referred to as a mesocrystal-is formed in which particles are crystallographically coaligned, but not in contact (12). In the second stage, the attachment barrier associated with the layer is overcome and particles fuse via a sudden "jump-to-contact" (5).…”
mentioning
confidence: 99%
“…Although the aggregation-based crystallization has been regarded as the actual crystallization mechanism for many inorganic crystals, however, few direct evidences exist that support the existence of such an intermediate stage. 19 Herein we report the observation of the primary nanoparticles in Na 2 SiF 6 , their self-assembly into loose aggregates, and subsequent crystallographic fusion and crystallization to generate final crystalline nanoplate or nanowire/nanorod. The complex Na 2 SiF 6 superstructures were also observed to form through similar processes.…”
mentioning
confidence: 98%